Strategi Komunikasi Pemasaran di Media Sosial Bidang Properti Atlantis Realty - Gunawan, Theodorus Axel; Rusdi, Farid (Kiwari, 2025)
The property business in the modern era can be considered one of the sectors that will never fade over time, as property is a fundamental necessity, comparable to the need for food. In today's digital era, social media plays a significant role in facilitating marketing communication across various industries, including the property business. With the presence of digital and social media, property marketing has become more effective and enables a wider reach in attracting consumers. Social media plays a crucial role in marketing communication strategies as it expands market coverage, making it easier to attract consumers in the sales process. This study uses a qualitative approach with in-depth interview data collection techniques. The findings of this study indicate that marketing communication at Atlantis Realty involves effective verbal communication techniques in product presentations, as well as the use of digital marketing on social media to reach a broader audience. The social media marketing team also implements strategies to ensure content appears on the FYP, such as understanding platform algorithms, creating engaging content, and using relevant hashtags. Bisnis properti di era modern saat ini dapat dikatakan sebagai salah satu sektor yang tidak akan lekang oleh waktu, karena properti merupakan kebutuhan dasar yang penting, sebanding dengan kebutuhan akan pangan. Di era digital sekarang ini, media sosial memainkan peran besar dalam mempermudah komunikasi pemasaran di berbagai bidang, termasuk dalam bisnis properti. Dengan hadirnya media digital dan sosial, pemasaran properti menjadi lebih efektif dan memungkinkan untuk memperluas jangkauan dalam menarik konsumen. Media sosial memiliki peran penting dalam strategi komunikasi pemasaran, karena dapat memperbesar cakupan pasar, sehingga mempermudah penyerapan konsumen dalam proses penjualan. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data wawancara mendalam. Hasil dari penelitian ini adalah marketing communication di Atlantis Realty melibatkan teknik komunikasi verbal yang baik dalam presentasi produk serta pemanfaatan digital marketing di media sosial untuk menjangkau audiens lebih luas. Tim social media marketing juga menerapkan strategi agar konten masuk ke FYP, seperti memahami algoritma platform, membuat konten menarik, serta menggunakan hashtag yang relevan.